Desain Advokasi Penyelesaian Pembiayaan Bermasalah Pada Baitul Maal Wa Tamwil - Supriyadi, Supriyadi; Hana, Kharis Fadlullah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
This study aims to determine the appropriate problem-solving model of financing. The research method used is socio-legal research. Researchers follow the activities of BMT practitioners and accommodate input from problems that occur. The object of this research is KSPPS Fastabiq Khoiru Ummah in the Kudus district. The study results show that in handling non-performing financing, preventive measures, monitoring, and handling are needed. This is related to the sustainability of KSPPS because the main objective is to channel the right financing and minimize non-performing financing. The recommendation of this research is to use a third party as an intermediary for the settlement. The closeness of employees with initially not problematic members makes members less responsive when resolved by the KSPPS. A third party in a legal aid institution is needed if the financing is difficult to resolve.